A New Repair Criterion for Inconel690 Alloy Steam Generator Tube with Fretting Wear. Issue 1 (June 2020) - Tao, Yuchun; Peng, Zhizhen; Kong, Chenguang; Huang, Song; Hui, Hu
Abstract: Structural integrity assessment of steam generator tubes(SGT) is important for the safety operation of pressurized water reactor. In this work, a repair criterion for Inconel690 SGT with fretting flaw was proposed. Firstly, experiments were conducted to address material strength, eddy current examination and bursting pressure of defected SGT. Then, a numerical method was proposed to predict bursting pressure. At last, all factors were concluded in a simplified statistical method of structural integrity assessment. For anti-vibration bar fretting, Condition Monitoring criterion, Operational Assessment criterion as well as the repair criterion for different inspection interval were proposed. The present criterion can provide reference for the inspection interval considering long-term temporary shutdown or standby.